Cortés- Justiniano - Cortés, Trinidad; Justiniano, Trinidad (Base Diseño e Innovación, 2016)
Cortes & Justiniano is a design studio oriented to the area of visual communication, specialized in the development of identity projects, print and publications of various formats. The studio faces each project as a particular design challenge where a collaborative experience is established with their clients. Together they develop the analysis and conceptualization, to generate, as a result of this process, relevant and creative communication solutions. The studio works with professionals in illustration, photography and web development, paying special attention to the production aspects, understanding technical specifications as resources that enhance the message.